Adding Value from Culture and Local Wisdom of Loincloth in Loei Province Toward Creative Economy - Phon-ngam, Patthira (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2019)
The purpose of this research was to create the value added of the loincloth products of the Ban Khamnerdpet weaving group of Loei Province. The focus was on the fabric design, pattern and processing of the loincloth. The research methodology which combined with those of the qualitative and the quantitative methods were used for data collection. The questionnaires were the tools to get the quantitative data. The in-depth interview, the focus group discussion, and the PAR workshop were the approaches for gaining the qualitative data. The population and sample of the quantitative study which was about need surveys consisted of the consumers who used loincloth products. Thetarget group for the qualitative research consisted of the Ban Khamnerdpet weaving group members, and members in villagers. Triangulation techniques were applied for the qualitative data validation. The statistics used for the quantitative data analysis were percentage and frequency. The content analysis was used for the qualitative data. The research found that the value added of the loincloth products of the Ban Khamnerdpet weaving group, the Thai Loei Pha Khaoma, was created through a fabric design showing the identity of the village called “Pet Nam Pao,” Nam Pao is the water resource which is a symbol of the community. For the processing, major products were as follows: (1) clothing, (2) supplies for homes, hotels and offices, (3) tableware, (4) decors for home, hotel and office, and (5) souvenirs. As for packaging, it was designed as a transparent plastic box. The box was in a rectangular shape.